Injection molding of high-precision optical lenses: A review - Peixoto, Carina; Valentim, Pablo T.; Sousa, Patrícia C.; Dias, Diana; Araújo, Cátia; Pereira, Diogo; Machado, Catarina F.; Pontes, Antonio J.; Santos, Hélio; Cruz, Sílvia (Precision engineering, 2022)
Injection molding (IM) is the most efficient mass production technology for manufacturing polymers in complex and detailed geometries with high precision. Although, with the demanding requirements for the optical components, the manufacturing process continues to be a challenge. The majority of optical components require high optical quality with low residual stress, high replication degree, and precisely controlled surface contours, which require a high control of the processing parameters and high-precision optical mold inserts. The main scope of this review is to describe recent progress in the IM, in particular, in the production of high-precision optical lenses. Thereby, an overview of the influence of process parameters, the emerging technologies able to improve the quality of molded components, and the fabrication technologies to produce optical inserts are provided. Furthermore, this review also reports the enhancement of optical performance by using optical coatings. Anti-reflective (AR) coatings, their fabrication techniques, as well as the methodologies typically employed for characterization are also addressed. [Display omitted] •Recent progresses on production of high-precision polymer optical lenses.•Influence of process parameters on the quality of polymer lenses.•Fabrication technologies to produce optical inserts.•Emerging technologies able to improve the quality of polymer lenses.•An overview on anti-reflective coatings, the recent advances, and its application.